Gender analysis: A review of mathematical problem-solving skills among madrasah tsanawiyah students - Nuralam Syamsuddin; Khairul Ismi; Devi Arhami Putri; Vina Hazaliyanti (State Islamic University of North Sumatra, 2026)
Mathematics problem-solving instruction should promote gender equality in schools. This study examined how gender relates to students' mathematical problem-solving processes in the context of the perimeter and area of plane figures. A descriptive qualitative design was employed to explore how students interpreted problems, selected strategies, and validated their solutions. Seventh-grade students from MTsN 2 Banda Aceh were purposively selected from Class VII-1 based on the results of an initial screening test. The participants consisted of two male and two female students representing high and low levels of problem-solving ability. Data were collected through an open-ended problem-solving test and semi-structured interviews. The data were analyzed using Miles and Huberman's interactive model, and the credibility of the findings was enhanced through time triangulation by administering comparable tasks on different occasions. The findings showed that female students tended to provide more complete representations of the given and required information and were more likely to review the plausibility of their answers. Male students generally performed calculations more quickly but often omitted the checking stage and occasionally skipped intermediate reasoning. Among students with low problem-solving ability, both males and females experienced difficulty planning effective solution strategies and connecting the given information with relevant geometric concepts. Gender differences were more evident in the quality of the problem-solving process than in the final answers. Therefore, mathematics instruction should emphasize explicit problem-solving routines, strategic planning, and systematic checking to support all learners.